The ecology of insect–yeast relationships and its relevance to human industry. Issue 1875 (28th March 2018) - Madden, Anne A.; Epps, Mary Jane; Fukami, Tadashi; Irwin, Rebecca E.; Sheppard, John; Sorger, D. Magdalena; Dunn, Robert R.
Abstract : Many species of yeast are integral to human society. They produce many of our foods, beverages and industrial chemicals, challenge us as pathogens, and provide models for the study of our own biology. However, few species are regularly studied and much of their ecology remains unclear, hindering the development of knowledge that is needed to improve the relationships between humans and yeasts. There is increasing evidence that insects are an essential component of ascomycetous yeast ecology. We propose a 'dispersal–encounter hypothesis' whereby yeasts are dispersed by insects between ephemeral, spatially disparate sugar resources, and insects, in turn, obtain the benefits of an honest signal from yeasts for the sugar resources. We review the relationship between yeasts and insects through three main examples: social wasps, social bees and beetles, with some additional examples from fruit flies. Ultimately, we suggest that over the next decades, consideration of these ecological and evolutionary relationships between insects and yeasts will allow prediction of where new yeast diversity is most likely to be discovered, particularly yeasts with traits of interest to human industry.